Soybean Cost-Return Budget in South Central Kansas - Dhuyvetter, Kevin C.; O'Brien, Daniel M.; Shoup, Douglas (My University, 2014)
This publication provides estimated cost and returns for forward farm planning for soybeans in south central Kansas.
MF2156_2014_02
Keywords: MF2156; Crops; Economics; MF